POSS-derived mesoporous ionic copolymer–polyoxometalate catalysts with a surfactant function for epoxidation reactions. (24th August 2015) - Zhao, Jiwei; Leng, Yan; Jiang, Pingping; Wang, Jun; Zhang, Chenjun
Abstract : Novel mesoporous POSS-derived POM-paired polymeric hybrids were demonstrated to be highly efficient interfacial solid catalysts for the epoxidation of alkenes with H2 O2 . Abstract : A series of novel polyoxometalate (POM)-based stable polymeric hybrids were successfully synthesized using polyhedral oligomeric vinylsilsesquioxanes (POSS) and ionic liquids (IL) bearing hydrophobic alkyl chains as the building blocks, followed by ion exchange with Keggin-type phosphotungstic acid (PW). The obtained hybrids POSS–IL x –PW were demonstrated to be mesostructured and amphiphilic materials with good thermal stability. Catalytic tests for the H2 O2 -based epoxidation of cyclooctene have shown that these newly designed catalysts exhibit extraordinary catalytic activities, catalytic rates, and quite stable reusability. The unique amphiphilic property and the mesoporous structure are revealed to be responsible for the catalysts' excellent performance in epoxidation reactions with H2 O2 .